PERNIKAHAN ANAK DI BAWAH UMUR DALAM PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - Fadel Muhammad Fadel; Muhammad Khairul Musthafa; Johari; Akbarizan (TERAJU: Jurnal Syariah dan Hukum, 2025)
This study analyses the marriage of minors (early marriage) through the perspective of Islamic law and the Indonesian Marriage Law (Law No. 1 of 2019), and examines the implications of differences in legal basis between the two. In this study, the author employs a qualitative research approach utilising normative legal research methods (library research). The analysis is conducted through the inventory, identification, and systematisation of primary (the Qur’an, hadith, law) and secondary (scientific literature) legal sources. Based on the discussion, it can be concluded that Islamic Law emphasises physical and mental readiness (baligh) and economic capability as prerequisites for marriage, without an absolute age limit. The sources of law are dynamic (the Qur’an, hadith, and the ijtihad of scholars), taking into account maslahat and the maqasid of Sharia. Indonesian Positive Law (Marriage Law) sets a rigid age limit (19 years for men, 16 years for women – revised to 19 years for both parties in 2019) which is based on material law (social norms, customs, child protection). Based on this, it can be concluded that although both legal systems are formally valid, the difference in legal sources (Sharia vs positivism) creates practical tensions. Policy recommendations call for the integration of the principles of maqasid sharia (protection of offspring, protection of the soul) with the protection of children’s rights in national law.